Magnetic Resonance Imaging and Magnetic Resonance Angiography Findings of External Carotid Artery Aneurysm and Coexisting Carotid Body Tumor. Issue 8 (November 2016) - Mutlu, Vahit; Ogul, Hayri
Abstract : Abstract: Carotid body tumors originate from paraganglionic tissue in the bifurcation of the common carotid artery. Magnetic resonance imaging is a frequently used diagnostic method in the preoperative diagnosis of these tumors and provides appropriate information for surgical planning. In this study, the authors emphasize magnetic resonance imaging and magnetic resonance angiography findings of the external carotid artery aneurysm associated with carotid body tumor. This highlights that the diagnosis of carotid artery aneurysms is essential to avoid accidental injury to the vessel during tumor surgery.